The Influence of Competence, Role of Village Apparatus and Understanding of Village Fund Management on Village Fund Management Accountability - Muhammad Dzulfikar Ardiansyah; Sriyono Sriyono (Universitas Muhammadiyah Sidoarjo, 2021)
Accountability within government agencies, the principles of accountability can be observed. This study aims to determine the effect of competence, the role of village officials and understanding of village fund management on the accountability of village fund management in Sidoarjo Regency. This research method uses quantitative, data collection is done by questionnaire. The sample that can be used as respondents is 75 respondents. The sampling technique used is purposive sampling. The analysis technique in this study is multiple linear regression analysis. The results showed that, Competence affects the accountability of village fund management in Sidoarjo Regency, the role of village officials affects the accountability of village fund management in Sidoarjo Regency and understanding has no effect on village fund management accountability in Sidoarjo Regency.